Workshop on Water, Culture, Language, and Native People in the Arctic (WOWCLAN), 2022 & 2023 ... - Anderson, John (Arctic Data Center, 2022)
The data archived was used to create the virtual Workshop on Water, Culture, Language, and Native People in the Arctic (WOWCLAN) Extended Reality (XR) workshop environments which also incorporated various publicly available sources published on the internet. These new workshop datasets included spatial scanning/environmental data (.glb), which facilitated the generation of 3D landscapes for three different XR-environments. Other data includes water quality sampling utilizing mobile application (HydroColor) water quality point source imagery in digital image (.png, .jpg) formats. Data displayed by HydroColor estimates the water turbidity (0-80 Nephelometric Turbidity Unit or NTU), concentration of suspended particulate matter (SPM) (grams per cubic meter or g/m^3) and the backscattering coefficient in the red (inverse meters or 1/m). Also included is location 360 imagery that offers immersive panoramic views, enriching the XR experience with diverse real-world locations. ...